Rapidly progressive dementia: probable sporadic Creutzfeldt–Jakob disease in a Yoruba Nigerian woman with rapidly progressive dementia: a case report - A. O. Idowu; A. F. Ogunmodede; A. A. Sanusi; U. C. Eke; S. A. Oyedele; M. B. Fawale; M. A. Komolafe (Journal of Medical Case Reports)
Abstract Background Creutzfeldt–Jakob disease is a neurodegenerative disorder that can present with neuropsychiatric features such as dementia; it is a rare cause of rapidly progressive dementia. There are no previously reported cases of probable or confirmed Creutzfeldt–Jakob disease in Nigeria. Case presentation A 68-year-old Nigerian Yoruba woman with known hypertension presented with a 6-week history of progressively worsening decline in memory, incoherent speech, irrational behavior, visual hallucinations, acute insomnia, and inability to independently perform activities of daily living. Examination revealed impairment in immediate recall, short- and long-term memories, and a Mini-Mental State Examination score of 2/30. She had an ataxic gait with abnormal jerky movements of the upper limbs. Brain magnetic resonance imaging and electroencephalography were consistent with Creutzfeldt‒Jakob disease. She subsequently experienced sudden clinical deterioration following seizure episodes and features suggestive of aspiration pneumonia, and she died within 14 weeks of the onset of the illness. Conclusion This case highlights the pattern and progression of Creutzfeldt–Jakob disease as a cause of dementia in an elderly Nigerian woman and the need to have a high index of suspicion of the diagnosis in patients presenting with rapidly progressive neuropsychiatric symptoms and dementia. Early diagnosis allows caregivers and patients to prepare well for the future, as the disease remains incurable.